Bimodal titanium alloys with ultrafine lamellar eutectic structure fabricated by semi-solid sintering. (15th June 2017) - Yang, C.; Kang, L.M.; Li, X.X.; Zhang, W.W.; Zhang, D.T.; Fu, Z.Q.; Li, Y.Y.; Zhang, L.C.; Lavernia, E.J.
Abstract: We report on a novel approach to synthesize (Ti100- x - y Fe x Co y )82 Nb12.2 Al5.8 (at.%) bimodal alloys and provide fundamental insight into their underlying microstructural evolution and mechanical behavior. In our work, a bimodal microstructure is attained via selection of phases and composition in a eutectic reaction followed by semi-solid sintering. Specifically, if one selects an atomic ratio of Ti/Fe corresponding to the eutectic composition, the resultant (Ti63.5 Fe26.5 Co10 )82 Nb12.2 Al5.8 alloy shows a bimodal microstructure of micron-sized fcc Ti2 (Co, Fe) embedded in an ultrafine lamellar eutectic matrix containing ultrafine bcc β-Ti and bcc B2 superstructured Ti(Fe, Co) lamellae. This structure forms from the complete eutectic reaction between β-Ti and Ti(Fe, Co). The phase boundary of β-Ti and Ti(Fe, Co) lamellae consists of a coherent interface with the orientational relationships: (110)β-Ti //(110)Ti(Fe, Co), (200)β-Ti //(100)Ti(Fe, Co) and ( 1 1 ¯ 0 ) β - Ti // ( 1 1 ¯ 0 ) Ti ( Fe, Co ) . Such bimodal alloy exhibits ultra-high compressive yield strength of 2050 MPa with a compressive plasticity of 19.7%, which exceed published values of equivalent materials. These unusual mechanical properties are attributed to a mechanism that involves blocking, branching and multiplication of β-Ti lamellae, dislocation interactions in Ti(Fe, Co) lamellae, and the stability of coherent interfaces. In addition, unusual phenomenon of introduced high-density dislocations in B2 superstructured Ti(Fe, Co) lamellae, other than β-Ti lamellae, can be rationalized based on the formation and decomposition of superlattice dislocations according to classic crystallographic strengthening theory. Graphical abstract: Bimodal titanium alloy with ultrafine lamellar eutectic matrix fabricated by semi-solid sintering exhibits ultra-high yield strength of 2050 MPa with plasticity of 19.7%, which exceed published values of equivalent materials. Also, it displays distinct yield phenomenon of a noticed tensile plastic strain and possesses an ultimate tensile stress of 920 MPa with a maximum elongation of 1.6%, approximately equivalent to those of cast bimodal titanium alloys. Image